Reduction of Growth and Reproduction of the Biotrophic Fungus Blumeria graminis in the Presence of a Necrotrophic Pathogen - Orton, Elizabeth S.; Brown, James K. M. (Frontiers in Plant Science, 2016)
Crops are attacked by many potential pathogens with differing life-history traits, which raises the question of whether or not the outcome of infection by one pathogen may be modulated by a change in the host environment brought on by infection by another pathogen. We investigated the host-mediated interaction between the biotroph Blumeria graminis f.sp. tritici (Bgt), the powdery mildew pathogen of wheat, and the necrotroph Zymoseptoria tritici, which has a long latent, endophytic phase following which it switches to a necrotrophic phase, resulting in the disease symptoms of Septoria tritici blotch. Both diseases are potentially severe in humid temperate climates and are controlled by fungicides and by growing wheat varieties with partial resistance. The compatible interaction between Z. tritici and the host reduced the number, size and reproductive capacity of mildew colonies that a normally virulent Bgt isolate would produce but did not significantly alter the early development of Bgt on the leaf. The effect on virulent Bgt was elicited only by viable spores of Z. tritici. Notably, this effect was seen before the necrotic foliar symptoms induced by Z. tritici were visible, which implies there is a physiological interaction during the latent, endophytic period of Z. tritici, which either takes place directly between this fungus and Bgt or is mediated by the wheat leaf. Information on how different pathogens interact in host plants may allow plant breeders and others to improve the design of screening trials and selection of germplasm.